2018
DOI: 10.1186/s12877-018-0988-8
|View full text |Cite
|
Sign up to set email alerts
|

Yoga to prevent mobility limitations in older adults: feasibility of a randomized controlled trial

Abstract: BackgroundThe loss of mobility during aging impacts independence and leads to further disability, morbidity, and reduced life expectancy. Our objective was to examine the feasibility and safety of conducting a randomized controlled trial of yoga for older adults at risk for mobility limitations.MethodsSedentary older adults (n = 46; age 60–89) were recruited and randomized to either yoga or a health education comparison group. Yoga sessions (60-min) occurred 2x weekly, and 90-min health education sessions occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…In total, 3224 participants aged 59 years and above (72.2 ± 7.3) were involved in the included 37 randomized controlled trials [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ] ( Table S1 ). The mean sample size was 93 ± 56.7 subjects ranging from 17 [ 74 ] to 269 [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 3224 participants aged 59 years and above (72.2 ± 7.3) were involved in the included 37 randomized controlled trials [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ] ( Table S1 ). The mean sample size was 93 ± 56.7 subjects ranging from 17 [ 74 ] to 269 [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mainly, the Tai Chi Yang style (24 forms or 10 simplified forms) was applied. Yoga was performed in 10 studies [ 49 , 50 , 64 , 65 , 67 , 70 , 71 , 72 , 74 , 77 ], whereas Qigong appeared in five study arms [ 70 , 73 , 79 , 81 ], Pilates three times [ 45 , 46 , 48 ] and Tai Chi Qigong only twice [ 68 , 76 ]. Each mind–body intervention was an isolated treatment given to the intervention group, except for one study that combined Tai Chi with cognitive behavioral strategies [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence suggests that yoga as an alternative and complementary therapy can also increase physical activity and reduce sedentary behavior (Lau et al, 2015). In addition to the beneficial yoga effects on flexibility and strength (Gothe, McAuley, 2016;Groessl et al, 2018), some yoga postures (asanas) may achieve the recommended level of intensity for endurance improvement (Hagins et al, 2007). Nevertheless, there is evidence that yoga can improve cardiovascular en-durance (Lau et al, 2015), however, to the best of our knowledge, no information is available regarding population aged 60 years and older.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted across the globe have demonstrated the positive effects of yoga on the number of health outcomes that concerns elderly such as improvements in depression and anxiety [13,[23][24][25][26][27], mood and stress [25,28], pain reduction [29,30], enhanced sleep quality [13,25,26,30,31], balance resulting in fall prevention [23,27,32,33] cognition [31,34] and cardio metabolic health [17,28,30,35]. Studies have also reported improvement in the subjective well-being [36,37].…”
Section: Introductionmentioning
confidence: 99%